Gear up : designing an ESP course for mechanical engineering students = Diseño de un curso ESP para estudiantes de ingeniería mecánica - Elizondo González, José Fabián 1987-
This article presents the design of the course Gear Up, an ESP course addressed to Mechanical Engineering students at the University of Costa Rica. To gather the necessary data, a needs analysis and a diagnostic test were conducted to determine the contents, macro-skills, and evaluated activities to be includedin the course. This article presents the findings of these two major initial activities and the subsequent course design proposal to satisfy the needs, wants, and lacks of both the students and stakeholders that participated in the process. Consequently, Gear Upwas created as a 16-week course in which the Task-Based Language Teaching approach would guide both the content and performance-based, assessed activities throughout the course.